2016
DOI: 10.1111/jcmm.12780
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin targets ERK2 and suppresses UVB‐induced photoaging

Abstract: A number of natural phytochemicals have anti‐photoaging properties that appear to be mediated through the inhibition of matrix metalloproteinase‐1 (MMP‐1) expression, but their direct target molecule(s) and mechanism(s) remain unclear. We investigated the effect of naringenin, a major flavonoid found in citrus, on UVB‐induced MMP‐1 expression and identified its direct target. The HaCaT human skin keratinocyte cell line and 3‐dimensional (3‐D) human skin equivalent cultures were treated or not treated with nari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Gold lotion (GL), a formulated product extracted from the peels of six citrus fruits (navel oranges, Citrus hassaku , Citrus limon , Citrus natsudaidai , Citrus miyauchi Iyo and Satsuma), has been developed in Japan. GL contains various flavonoids that have potential to protect the skin against UV‐induced damage and aging . In addition to skin protection, GL has also been demonstrated to suppress azoxymethane‐induced aberrant crypt foci formation in mice by downregulating inflammation‐related protein levels that may subsequently prevent inflammation‐associated colon tumorigenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Gold lotion (GL), a formulated product extracted from the peels of six citrus fruits (navel oranges, Citrus hassaku , Citrus limon , Citrus natsudaidai , Citrus miyauchi Iyo and Satsuma), has been developed in Japan. GL contains various flavonoids that have potential to protect the skin against UV‐induced damage and aging . In addition to skin protection, GL has also been demonstrated to suppress azoxymethane‐induced aberrant crypt foci formation in mice by downregulating inflammation‐related protein levels that may subsequently prevent inflammation‐associated colon tumorigenesis .…”
Section: Introductionmentioning
confidence: 99%
“…48,49 NG inhibited UVB-induced ERK2 activity by binding to ERK2 and had anti-aging effects. 49 NG bound to phosphoinositide 3-kinase, increased phosphoinositide 3-kinase inhibition activity, and had anti-cancer effects. 50 Thus, we speculate that the regulatory effects of NG would be the results of its binding to various receptors or intracellular signalling molecules.…”
Section: Discussionmentioning
confidence: 98%
“…Immunosuppressive activity of NG was regulated by its direct interaction with the ligand‐binding site of aryl hydrocarbon receptor . NG was also found to enter cells, interact with intracellular signalling molecules, and thus, regulate signalling . NG inhibited UVB‐induced ERK2 activity by binding to ERK2 and had anti‐aging effects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Jung et al . reported that naringenin suppressed UVB‐induced MMP‐1 expression via ERK/AP‐1 signaling pathway in keratinocytes. Similarly, our results also suggested that treatment of naringenin quenched the UVB irradiation‐induced increase of MMP‐1 mRNA in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%